The Relationship between Maternal Perception and Complete Basic Immunization Status in Toddlers in Primary Health Care in Garut City - Widadi, Sri Yekti; Kurniasih, Nunung (Media Publikasi Cendekia Indonesia, 2025)
Basic immunization coverage remains a challenge in Indonesia's public health efforts despite being a national priority program. Maternal perception is considered one of the factors that influence the completeness of immunization in children. Maternal perceptions of immunization can play an important role in determining the completeness of child immunization, as the decision to provide immunization is often influenced by the mother's beliefs and knowledge about the benefits of vaccines. This study aims to determine the relationship between maternal perceptions and the completeness of basic immunization status in toddlers in primary health care. This study is a quantitative study with a cross-sectional design involving 69 mothers who have children aged 9-24 months. Respondents were selected using a quota sampling technique. Data were collected through a standardized and validated questionnaire in the Indonesian version. The data were analyzed univariately using frequency distribution and bivariately with the Chi-Square test. Most mothers (94.2%) had a positive perception of immunization, and 72.46% of children had received complete basic immunization. However, the results of statistical analysis showed no significant relationship between maternal perceptions and completeness of basic immunization (p = 0.3; OR= 0,31). Although the majority of mothers had positive perceptions, it was not significantly associated with children's basic immunization status. This finding indicates that other factors, such as vaccine availability, access to health services, and social support, may have a greater role in influencing immunization practices.